A PENGARUH KUALITAS PELAYANAN SIAKAD DAN SISTEM INFORMASI TERHADAP KEPUASAN MAHASISWA INSTITUT TEKNOLOGI BATAM: Jurnal Sistem Informasi - nazir, muhamad; Muhammad Jufri (JURNAL SITEBA, 2023)
The research location is in the Faculty of Information Technology, Information Systems Study Program, Batam Institute of Technology. The research object is SIAKAD users, namely students and lecturers. This study aims to determine student satisfaction with the SIAKAD website at Batam Institute of Technology. To determine the level of student satisfaction with SIAKAD, the data and method used is the data processed from the questionnaire filled out by 5th-semester information system students in 2022.